The three Rs along the TRAIL: Resistance, re-sensitization and reactive oxygen species (ROS) - Mellier, G.; Pervaiz, Shazib (2012)
Ligation of the Tumour necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) death receptors has been associated with cancer specific apoptotic execution in a number of model systems. This has generated tremendous interest in the use of TRAIL as a potential therapeutic modality. However, recent evidence indicates that resistance to TRAIL might present with a therapeutic challenge. In this short report, we review the basic biology of TRAIL signalling in cancer cells, highlight the mechanisms underlying resistance to TRAIL and the ability of small molecule compounds to re-sensitize cells to TRAIL-mediated apoptosis. In particular, we provide evidence that intracellular reactive oxygen species could be critical in regulating the response of cancer cells to TRAIL. © 2012 Informa UK, Ltd.